Adsorbent Precoating by Lyophilization: A Novel Green Solvent Technique to Enhance Cinnarizine Release from Solid Self-Nanoemulsifying Drug Delivery Systems (S-SNEDDS) - Ahmad Yousef Tashish; Ahmad Abdul-Wahhab Shahba; Fars Kaed Alanazi; Mohsin Kazi (MDPI AG, 2022)
Background: Solidification by high surface area adsorbents has been associated with major obstacles in drug release. Accordingly, new approaches are highly demanded to solve these limitations. The current study proposes to improve the drug release of solidified self-nanoemulsifying drug delivery systems (SNEDDS) to present dual enhancement of drug solubilization and formulation stabilization, using cinnarizine (CN) as a model drug. Methods: The solidification process involved the precoating of adsorbent by lyophilization of the aqueous dispersion of polymer-adsorbent mixture using water as a green solvent. Then, the precoated adsorbent was mixed with drug-loaded liquid SNEDDS to prepare solid SNEDDS. The solid-state characterization of developed cured S-SNEDDS was done using X-ray powder diffraction (XRD) and differential scanning calorimetry (DSC). In vitro dissolution studies were conducted to investigate CN SNEDDS performance at pH 1.2 and 6.8. The solidified formulations were characterized by Brunauer-Emmett-Teller (BET), powder flow properties, scanning electron microscopy, and droplet size analysis. In addition, the optimized formulations were evaluated through in vitro lipolysis and stability studies. Results: The cured solid SNEDDS formula by PVP k30 showed acceptable self-emulsification and powder flow properties. XRD and DSC revealed that CN was successfully amorphized into drug-loaded S-SNEDDS. The uncured solid SNEDDS experienced negligible drug release (only 5% drug release after 2 h), while the cured S-SNEDDS showed up to 12-fold enhancement of total drug release (at 2 h) compared to the uncured counterpart. However, the cured S- SNEDDS showed considerable CN degradation and decrease in drug release upon storage in accelerated conditions. Conclusions: The implemented solidification approach offers a promising technique to minimize the adverse effect of adsorbent on drug release and accomplish improved drug release from solidified SNEDDS.